Dental students' self-perception : health and academics during COVID-19 quarantine = Autopercepción de los estudiantes de Odontología : salud y vida académica durante la cuarentena por COVID-19 - Frias, Emilio; López Santacruz, Hiram Daniel; Ayala Herrera, José Luis (2021)
The aim of this study was to analyze the self-perceived general health, oral care, stress, academic environment, and harmful habits of Mexican dental students during the COVID-19 quarantine period. This descriptive observational study consisted of a self-perception survey that was sent to dental students undergoing virtual classes. Five sections were analyzed: General Health, Oral Health, Stress, Academic Environment and Habits. For each question, students were asked to rate their perception prior to, and during the contingency, which allowed a comparison to be made between both times for each inquiry. The answers were collected into Microsoft Excel and the statistical analyses were performed using SPSS v.20. A statistically significant difference was observed between the academic years for the variables: "physical exercise" prior to quarantine, "emotional problems" and "work-load" during quarantine, and "academic efficiency" for both times. A trend towards unfavorable perception in relation to general health, academic environment, and harmful habits was observed among dental students during social isolation derived from the pandemic. It is notable that 1st-year students presented a greater impact on all the variables of interest.
El propósito de este estudio fue analizar la autopercepción sobre salud general, cuidado oral, estrés, ambiente académico y hábitos nocivos de estudiantes de Odontología en México durante el periodo de cuarentena por COVID-19. Estudio descriptivo observacional que consistió en una encuesta de autopercepción enviada a estudiantes de Odontología que cursaban clases virtuales. Fueron analizadas cinco secciones: Salud General, Salud Oral, Estrés, Ambiente Académico y Hábitos. Para cada pregunta, se les pidió a los estudiantes que calificaran su percepción antes de, y durante la contingencia, lo que permitió realizar una comparación entre ambos tiempos para cada cuestión. Las respuestas fueron recolectadas en Microsoft Excel y los análisis estadísticos se realizaron empleando SPSS v.20. Una diferencia estadísticamente significativa fue observada entre los grados académicos, para las variables: "ejercicio físico" antes de la cuarentena, "problemas emocionales" y "carga de trabajo" durante la cuarentena, y "eficiencia académica" para ambos tiempos. Se observó una tendencia hacia una percepción desfavorable con relación a la salud general, ambiente académico y hábitos nocivos entre los estudiantes de Odontología, durante el aislamiento social derivado de la pandemia. Es notable que los alumnos de 1er año presentaron un mayor impacto en todas las variables de interés.
En revista Odóvtos, vol. 23, no.3 (septiembre-diciembre 2021)
Descripción basada en el contenido visto el 14 de noviembre, 2024
También disponible en formato HTML y EPUB